Business schools, the anxiety of finance, and the order of the 'middle tier'. Issue 1 (2nd January 2018) - Ortiz, Horacio; Muniesa, Fabian
ABSTRACT: Financial imagination plays a fundamental, yet ambivalent role in the establishment of hierarchies within and between business schools, and in business life at large. This study examines this process in the 'middle tier' of business education: that is, in the social space in which students and instructors understand themselves to occupy a 'mid-range' position within an order of excellence and success. Largely articulated through business school rankings, this order strongly relies on the centrality of the financial curriculum, proficiency in which is understood as both a proxy for smartness and a sign of moneymaking capacity. In the 'middle tier', this order manifests in the form of an anxiety: an order that, though legitimate, is thought not to be attained, or hardly attainable. The study draws from ethnographic investigation in a 'middle tier' business school with attention to how finance is made sense of in relation to an alternative curriculum, and in connection with the aim of 'making it to the top'. A comparison with a 'top tier' business school allows furthering understanding of how the order of business schools relies on the anxiety of finance in order to reproduce an acquiescence to dominant financial imagination.